Review of predicting the blast-induced ground vibrations to reduce impacts on ambient urban communities. (1st July 2020) - Yan, Yu; Hou, Xiaomeng; Fei, Honglu
Abstract: Drilling and blasting is widely used in mining and construction industries, and ground vibration is one of the detrimental effects caused by blasting. To determine the fragmentation of rocks and to ensure the safety of ambient urban areas and residents, it is necessary to determine the parameters that have a reasonable influence on blast-induced vibration. This review firstly presents the mechanism of influential parameters governing the ground vibration. The collected results show that these parameters such as free faces, decoupling, hole diameter, hole depth, charge type, delay blasting and geological conditions affect the prediction of ground vibration. Meanwhile, the influence of burden and hole numbers on the ground vibration is controversial in the current literature, and the few studies on the stemming and spacing are not enough to prove the impact of these factors on the prediction of peak particle velocity. While several methods are used for predicting ground vibration, four methods are summarized in this review, namely, empirical equation, AI algorithm, multiple regression analysis and numerical simulation methods. The details of the four methods for predicting the blast-induced vibration are discussed. Finally, performance assessments and sensitivity analysis are described, respectively, to compare the four methods for the accuracy of predicting the blast-induced vibration and to evaluate the effectiveness of various parameters in predicting the PPV. Graphical abstract: Image 1 Highlights: Ground vibration is one of serious environmental problems and need to be accurately predicted. Relevant parameters have an impact on blasting vibration were summarized. Empirical equations, AI models, numerical simulation and multiple regression analysis for predicting PPV were established.